The flow of management ideas: Rethinking managerial audiences - HEUSINKVELD, Stefan (Institutional Knowledge at Singapore Management University, 2021)
The widespread promotion of management ideas, their regular inclusion in textbooks and business school curricula and their use in organizational change programs has engendered debates about the impact of these ideas on management and organizational practice. Based on analyses of managerial audience members' activities and related meaning-making prior to, during and after guru events with leading management thinkers, this book sheds new light on how management practitioners come to use management ideas in the different relevant contexts of their working lives. The authors argue that a broader, more differentiated and more dynamic view of managerial audiences is essential in understanding the impact of management ideas as well as the nature of contemporary managerial work. For scholars and students in organisation studies, knowledge management and management consultancy, as well as reflective management practitioners.